Peran Pemoderasian Faktor Personal dan Situasional pada Hubungan Abusive Supervision dengan Anteseden dan Konsekuensinya - , FENIKA WULANI, Dr. T. Hani handoko, MBA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study examined the relationship of abusive supervision with its antecedents and consequences. Negative affectivity (NA) was tested as an antecedent, while workplace deviance behaviors (interpersonal deviance, organizational deviance and supervisor-directed deviance) and organizational citizenship behavior (OCB) were tested as its consequences. This study also considered the moderating role of leader-member exchange (LMX) on the relationship between abusive supervision and NA, the moderating role of trait anger and power distance orientation on the relationship between abusive supervision and workplace deviance behavior and the moderating role of impression management motive on the relationship between abusive supervision and OCB. In contrast to previous studies of abusive supervision that most of those research using a scale of uni-dimensional from Tepper (2000), this study used the three-dimensional scale of abusive supervision resulting from an exploratory study in Indonesia. The respondents of this study were 706 full-time and non-managerial employees working as a nurse and medical support in the hospital / health services